2022
DOI: 10.3389/fcvm.2022.838473
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Patients With Unexplained Syncope and Bundle Branch Block: Lower Risk of AV Block and Lesser Need for Cardiac Pacing in Women

Abstract: Graphical AbstractRisk of AVB and need for cardiac pacing. Left: Percentage of patients diagnosed with aAVB/sCD in both sexes. Right-top: Multivariate logistic regression analyses for risk of aAVB/sCD. Odds ratio and 95% CI are plotted. Right-bottom: Kaplan-Meier pacemaker-free survival estimates curves in both sexes. aAVB/sCD, advanced atrio-ventricular block or severe conduction disturbances; HR, hazard ratio; CI, confidence interval; y.o, years old; IHD, ischemic heart disease; LVEF, left ventricular ejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This study found that the diagnostic approach is safe and achieves a high rate of etiological diagnosis allowing for the selection of specific treatment and avoiding the implantation of unnecessary pacemakers. The results of the B4 study have been confirmed by several subsequent studies, some of them with a relatively high number of patients and long-term follow-up[ 80 , 108 , 132 - 134 ].…”
Section: Arrhythmic Syncope In Specific Populationsmentioning
confidence: 54%
“…This study found that the diagnostic approach is safe and achieves a high rate of etiological diagnosis allowing for the selection of specific treatment and avoiding the implantation of unnecessary pacemakers. The results of the B4 study have been confirmed by several subsequent studies, some of them with a relatively high number of patients and long-term follow-up[ 80 , 108 , 132 - 134 ].…”
Section: Arrhythmic Syncope In Specific Populationsmentioning
confidence: 54%
“…We assessed 37 studies by full‐text review. Finally, 5 prospective 12 , 21 , 22 , 23 , 24 and 5 retrospective 25 , 26 , 27 , 28 , 29 observational studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…As it shown in Table 1 , four studies were conducted in Japan 22 , 27 and Spain. 23 , 24 Other article's origins were Canada, 21 South Korea, 29 Italy, 28 Germany, 25 Slovakia, 26 and Australia. 12 The follow‐up time ranged from 3 months to over 3 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations